The Rhetorical Moves and Verb Tense in Research Article Abstracts - Mufidah Yusroh (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2017)
This study aims to examine the rhetorical moves and explore the use of verb tense in research article abstracts. This study employs corpus based approach using a corpus toolkit AntConc 3.2.4w. The subjects of this study are 29 research articles. The findings reveal that the preferred rhetorical moves of the abstracts are Move 2-purose, Move 3-method, and Move 4-result. The use of present tense is dominant in all five moves. Additionally, past tense is mostly found in method move. In this case, the writers employ the preferred rhetorical move and different verb tense in each move to emphasize the writer’s objectiveness.